2011
DOI: 10.1111/j.1439-037x.2011.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cl−/Salt Tolerance and NaCl-Induced Alternations of Tissue and Cellular Ion Fluxes in Glycine max, Glycine soja and their Hybrid Seedlings

Abstract: The salt‐sensitive Glycine max N23674 cultivar, the salt‐born Glycine soja BB52 population, and their hybrid 4076 strain (F5) selected for salt tolerance generation by generation were used as the experimental materials in this study. First, the effects of NaCl stress on seed germination, tissue damage, and time‐course ionic absorption and transportation were compared. When qualitatively compared with seed germination appearance in culture dishes, and tissue damages on roots or leaves of seedlings, or quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 18 publications
2
45
0
9
Order By: Relevance
“…A tolerância das plantas à salinidade requer, dentre vários fatores, a compartimentação de íons Na + e Cl -nos tecidos, a níveis intra/extracelular, a fim de evitar concentrações tóxicas dentro do citoplasma, especialmente nas células do mesofilo foliar (ZHANG et al, 2011 A tolerância das plantas à salinidade requer, dentre vários fatores, a compartimentação de íons Na + e Cl -nos tecidos, a níveis intra/extracelular, a fim de evitar concentrações tóxicas dentro do citoplasma, especialmente nas células do mesofilo foliar (ZHANG et al, 2011). Na maioria das culturas, tais como algodão, feijão, trigo e arroz, o Na + parece contribuir mais do que o Cl -para a toxidez em plantas sob estresse salino.…”
Section: Fonte: Elaboração Dos Autoresunclassified
See 2 more Smart Citations
“…A tolerância das plantas à salinidade requer, dentre vários fatores, a compartimentação de íons Na + e Cl -nos tecidos, a níveis intra/extracelular, a fim de evitar concentrações tóxicas dentro do citoplasma, especialmente nas células do mesofilo foliar (ZHANG et al, 2011 A tolerância das plantas à salinidade requer, dentre vários fatores, a compartimentação de íons Na + e Cl -nos tecidos, a níveis intra/extracelular, a fim de evitar concentrações tóxicas dentro do citoplasma, especialmente nas células do mesofilo foliar (ZHANG et al, 2011). Na maioria das culturas, tais como algodão, feijão, trigo e arroz, o Na + parece contribuir mais do que o Cl -para a toxidez em plantas sob estresse salino.…”
Section: Fonte: Elaboração Dos Autoresunclassified
“…Na maioria das culturas, tais como algodão, feijão, trigo e arroz, o Na + parece contribuir mais do que o Cl -para a toxidez em plantas sob estresse salino. Contudo, existem estudos que demonstram que algumas culturas (soja e citros, por exemplo) são mais sensíveis ao Cl -do que ao Na + (BRUMÓS et al, 2009;LUO;LIU, 2005;ZHANG et al, 2011).…”
Section: Fonte: Elaboração Dos Autoresunclassified
See 1 more Smart Citation
“…The absorbed nitrogen for plants utilization includes various N forms (nitrate, ammonium, amino acids, and peptides), and nitrate (NO 3 -) is the most important nitrogen source for plants (Chen et al, 2012), and is also the main mineral and univalent anions in plant tissues and cells except Cl -, 2010). Studies have showed that, tobacco, grape, potato, citrus and soybean, whose salt stress effects are mainly caused by Cl -, are known as the "chloridehating plants" (Zhang et al, 2011, Abbaspour et al, 2013, Henderson et al, 2014. Cultivated soybean (G. max) is one of the important grain and oil crops in the world, wild soybean (G. soja) is the relative of G. max, and is often regarded as an important genetic germplasm resource for high yield and good quality of G. max breeding (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that, tobacco, grape, potato, citrus and soybean, whose salt stress effects are mainly caused by Cl -, are known as the "chloridehating plants" (Zhang et al, 2011, Abbaspour et al, 2013, Henderson et al, 2014. Cultivated soybean (G. max) is one of the important grain and oil crops in the world, wild soybean (G. soja) is the relative of G. max, and is often regarded as an important genetic germplasm resource for high yield and good quality of G. max breeding (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%